Analisis Minat Bermain pada Gim DOTA 2 dengan Metode Game Design Factors - Moch Meidhike Wirazitanra Jayadi; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Defense of Ancient 2 (DOTA 2) is PC game application with Multiplayer Online Battle Arena (MOBA) genre. This game application has 900 thousand daily active users in 2019. To know the reason behind the high number of actove players in DOTA2 game application, it is very important to collect information so that an evaluation of the behavior of gamers can be carried out which is divided into 2 parties. The first parties are people who play DOTA2 but haven't played other MOBA game applications. The second parties are people who play DOTA 2 but have played other MOBA game applications. Mixed methods will be used to collect information, especially qualitative interviews and quantitative questionnaires based on game design factors. After collecting information, an evaluation can be carried out to find differences in the size of the mean value of the questionnaire between the 2 parties and to find the relationship between the questionnaire scores and the result of the intervews so that conclusions can be drawn. The results of the questionnaire evaluation between 2 parties resulted in 11 statements of insignificant differences and 24 which had a significant difference, then the results from the interview of respondents proved that game design factors have reasons and impacts with the large number of active players in the DOTA2 game application.